2015
DOI: 10.1177/0333102415597527
|View full text |Cite
|
Sign up to set email alerts
|

Laser-evoked potential habituation and central sensitization symptoms in childhood migraine

Abstract: Abnormalities of pain processing and symptoms of central sensitization appear to be characteristics of children with migraine. Reduced habituation and progressive amplification of cortical responses to laser stimuli indicate an overactive nociceptive system at the onset of migraine, and this hyperactivity may subtend allodynia and pericranial tenderness. Future prospective trials may aid in the early identification of clinical phenotypes that display a tendency to develop into the chronic form of migraine, war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…In a recent study on pain-related evoked potentials in children with migraine, we observed reduced habituation of the cortical responses to pain, which was correlated with allodynia [16]. This latter symptom was found in almost all patients, suggesting a higher representation in the juvenile migraine than in the adult form [16]. …”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In a recent study on pain-related evoked potentials in children with migraine, we observed reduced habituation of the cortical responses to pain, which was correlated with allodynia [16]. This latter symptom was found in almost all patients, suggesting a higher representation in the juvenile migraine than in the adult form [16]. …”
Section: Introductionmentioning
confidence: 86%
“…The diagnosis of migraine was confirmed on the basis of at least 3 months of observation preceding the first visit. Upon the first visit reservation, the hospital staff gave parents the headache diary and the questionnaire of allodynia in the adult version [10, 16], to be presented during the first clinical approach at our Center (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations